Visualization of coronary artery calcification and its impact on percutaneous coronary intervention procedure (a literature review) - V. O. Hubka; Yu. M. Vailo; A. M. Materukhin; A. L. Makarenkov (Zaporožskij Medicinskij Žurnal)
In general, the phenomenon of vascular calcification is quite common and might pose considerable impediments for vascular, cardiovascular and endovascular surgeons, as well as for interventional cardiologists when performing surgical manipulations during the treatment of patients with coronary artery disease (CAD) or peripheral atherosclerosis. A high degree of coronary artery (CA) calcification is independently associated with an increased risk of major cardiovascular events after percutaneous coronary intervention (PCI).